Land Use Change and Future Prediction in Banggai Islands Regency, Central Sulawesi, Indonesia - Katili, Hidayat Arismunandar; Syartinilia; Irmansyah, Firman; Widiatmaka (Pusat Penelitian Lingkungan Hidup, IPB (PPLH-IPB) dan Program Studi Pengelolaan Sumberdaya Alam dan Lingkungan, IPB (PS. PSL, SPs. IPB), 2025)
Land use and land cover (LULC) changes can influence policies in a region due to economic and social conditions caused by population growth. The objective of this study is to analyze and map LULC changes in 2002, 2012, and 2022 using the Random Forest approach on Google Earth Engine, and to predict land use in 2042 using Markov-CA, thereby supporting the provision of accurate and sustainable policy data related to LULC in Banggai Islands Regency. This method can provide accurate information about the spatial distribution of rational LULC, balancing development demands with sustainable environmental protection. The study's results indicate that LULC has undergone significant changes from 2002 to 2022. There has been an increase in plantation land, open land, and settlements originating from forest and scrubland. Predictions of LULC changes in 2042 show an increase in plantations, settlements, and open land, while other land uses are declining. Effective land use policies require spatial planning that considers the potential andlimitations of land, as well as the space needs for residential, agricultural, and forest areas. This approach will facilitate the application of land conservation principles in sustainable, balanced agricultural and non-agricultural development in Banggai Islands Regency.